Aggregation of institutional repositories for the analysis of the scientific performance of Peruvian universities - Valles-Coral, Miguel; Injante, Richard; Hernández-Torres, Edwin; Pinedo, Lloy; Navarro-Cabrera, Jorge Raul; Salazar-Ramírez, Luis; Cárdenas-García, Ángel; Huancaruna, Eddy (Iberoamerican Journal of Science Measurement and Communication, 2023)
Objective. The scientific performance of Peruvian universities was examined and characterized by aggregating information from their institutional repositories. Design/Methodology/Approach. A protocol was followed that included the following stages: (1) analysis and optimization of the DSpace database model; (2) data recovery and validation with the OAI-PMH Protocol; (3) obtaining an index of resources available in the repositories; (4) metadata extraction and processing; and (5) extraction and inclusion of keywords in the database. Results/Discussion. A diverse use of keywords was identified. 69,1% of them appeared only once. A significant gap was evident in producing theses between public and private universities. Conclusions. The discrepancy between the research areas of Peruvian universities and regional needs highlights the importance of greater alignment between academic production and the demands of society in each region; this underlines the need to adapt research programs to address specific problems and contribute more effectively to regional development.